Objective structured practical examination as a formative assessment tool compared to traditional method for third year M.B.B.S. community medicine students - Carolin, Archana; Venkata Devi, Prathyusha Tirupati (International Journal Of Community Medicine And Public Health, 2019)
Background: Assessment of students in medical colleges was done by traditional practical examination for evaluation of practical or clinical skills, which is subjective in nature and suffer from lack of objectivity. So a uniform system of clinical and practical evaluation of medical students is always desirable. An objective structured practical examination (OSPE) is one such method believed to meet the deficiencies of the conventional system of practical/clinical examination. This study is an attempt to evaluate the effectiveness of OSPE as a formative assessment tool compared to traditional methods for M.B.B.S. students. Methods: A cross sectional comparative study was carried out on 56 MBBS students in KAMSRC, Hyderabad, Telangana. Students of 3rd year M.B.B.S were subjected to traditional practical evaluation followed by OSPE. A eight station OSPE was conducted one week after the TPE. The scores obtained in both were compared. All the data collected was entered and analyzed with MS excel software 2007. Results: Average marks scored by the students in OSPE (17.78±2.69) were higher as compared to traditional practical examination (15.00±3.49) which was statistically significant. 74.4% of the students strongly agreed that OSPE is fairer in comparison to traditional practical examination. 90.5% students strongly agreed that variability of examiner and patient can be removed to a large extent by OSPE. Conclusions: Based on the observation, OSPE was found to be a more effective assessment tool than traditional method.